THE INNOVATIVE WORK BEHAVIOR OF SECOND-GENERATION LEADERS: THE CASE OF FAMILY BUSINESS - Kurniawan, Daniel; Tambunan, Damelina Basauli (Universitas Brawijaya, Indonesia, 2022)
Innovation has been proven to be one of the main keys to reaching sustainability. This study aims to analyze the impact of creative self-efficacy and organizational climate for innovation on innovative work behavior in the family business setting to enrich the studies of innovation in the family business. This study also tests the indirect effect of Entrepreneurial Leadership in increasing the impact of creative self-efficacy on innovative work behavior. This study uses the quantitative method by delivering questionnaires to more than 400 family firms in Surabaya. This study indicated that creative self-efficacy and organizational climate for information positively and significantly impact innovative work behavior. However, the impact of creative self-efficacy on innovative work behavior is stronger than the organizational climate for innovation. This study also proves the impact of creative self-efficacy on innovative work behavior will increase by enhancing entrepreneurial leadership. The implications of this study also are discussed both academically and practically.